Dampak Hukum Dari Akibat Putusnya Perkawinan Pasangan Berbeda Agama Terhadap Harta Bersama Dan Hak Asuh Anak - Deva Tri Ananda; Lukmanul Hakim; Ansori Ansori (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
Indonesia is known for its diverse cultures and customs that have been ingrained from their ancestors. Where different religions and beliefs have different rules regarding marriage. This social interaction can give rise to a relationship that can continue into marriage. Marriage is a religious thing where a relationship between two human beings, namely a man and a woman who have grown up, have the desire to unite and promise in a sacred bond as husband and wife to form a happy, harmonious family and multiply offspring. The aim of this research is to determine the legality of marriage between couples of different religions according to Islamic law and the Marriage Law (in Decision Number 8/Pdt.G/2022/PN Tjk) as well as the position of joint assets after the dissolution of marriage for couples of different religions after the marriage was decided according to law. Islam and according to the Marriage Law (In Decision Number 8/Pdt.G/2022/PN Tjk). The results of this research indicate that the validity of interfaith marriages based on Decision Number 8/Pdt.G/2022/PN Tjk is clearly prohibited from a positive legal perspective in Indonesia, both in the Compilation of Islamic Law (KHI) and Law Number 1 of 1974 concerning Marriage. . Furthermore, in connection with this decision, the Panel of Judges gave sanctions to the Plaintiff to pay court costs in the amount of Rp. 845,000.00 (eight hundred and forty five thousand rupiah) and stated that the Plaintiff was on the losing side. The position of joint property after the dissolution of an interfaith marriage when viewed from the perspective of the Compilation of Islamic Law in accordance with Article 97 is that the division of joint property in the event of a divorced husband and wife prioritizes the method of peace (deliberation). Then in Law no. 1 of 1974 and the Civil Code Law in article 37 of Law no. 1 of 1974 and articles 128-129 of the Civil Code that if the marriage bond between husband and wife is broken, then the joint assets are divided between the husband and wife. However, in law, rules are used as long as the parties do not determine otherwise or the rules are regulated according to their respective laws. In connection with the study of decision Number 8/Pdt.G/2022/PN.Tjk, because in the facts of the trial in this case the Defendant had been baptized, the division of assets was based on Law No. 1 of 1974 and the Civil Code, and because both parties do not have joint assets but have a debt which was incurred by the defendant by falsifying their identity due to pressure due to the plaintiff's actions which did not provide maintenance, the judge's decision was to settle the debt after the divorce in a joint manner. Jointly is the right decision.